DELIRIUM PADA ENSEFALOPATI HEPATIK STADIUM LANJUT DENGAN RIWAYAT PENGGUNAAN METAMFETAMIN: TANTANGAN DIAGNOSTIK DAN TERAPI - Nahusona, Gladya Florenscia Anggelly; Aryani, Luh Nyoman Alit (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
Delirium is an acute neuropsychiatric condition characterized by disturbances in consciousness, attention, and cognition, which often develops over a short period due to serious medical conditions, including hepatic encephalopathy. Advanced-stage hepatic encephalopathy (stage III–IV) is typically associated with liver cirrhosis and elevated ammonia levels, and may be precipitated by factors such as infection, gastrointestinal bleeding, or psychoactive substance use. We report a case of delirium in a patient with stage III hepatic encephalopathy and a history of methamphetamine use under a harmful use pattern, currently in early remission. The coexistence of systemic metabolic dysfunction due to liver failure and the neurotoxic effects of stimulant abuse complicates the clinical presentation and management. Comprehensive clinical, psychiatric, and toxicological assessment is essential for accurate diagnosis. Management includes supportive therapy for hepatic encephalopathy, addiction-focused psychiatric care, and family education. This case underscores the importance of interdisciplinary collaboration in managing delirium in patients with comorbid substance use disorders, and emphasizes the need for a biopsychosocial approach to long-term recovery planning. ABSTRAKDelirium merupakan gangguan neuropsikiatri akut yang ditandai oleh gangguan kesadaran, perhatian, dan kognisi, yang dapat berkembang dalam waktu singkat akibat berbagai kondisi medis serius, termasuk ensefalopati hepatik. Ensefalopati hepatik stadium lanjut (stadium III–IV) sering kali berkaitan dengan sirosis hati dan peningkatan kadar amonia, serta dapat diperberat oleh faktor presipitasi seperti infeksi, perdarahan saluran cerna, dan penggunaan zat adiktif. Kami melaporkan kasus seorang pasien dengan delirium et causa ensefalopati hepatik stadium III yang juga memiliki riwayat penggunaan metamfetamin dengan pola penggunaan yang merugikan (harmful use) dan berada dalam masa remisi awal. Kombinasi antara gangguan metabolik sistemik akibat disfungsi hepatik dan efek neurotoksik dari penggunaan stimulan memperumit perjalanan klinis pasien. Diagnosis memerlukan evaluasi menyeluruh secara klinis, psikiatrik, dan toksikologis. Penanganan melibatkan terapi suportif untuk ensefalopati, pendekatan psikiatri adiksi, serta edukasi keluarga. Laporan kasus ini menunjukkan pentingnya kolaborasi lintas disiplin dalam menghadapi kasus delirium pada pasien dengan komorbiditas gangguan penggunaan zat, serta perlunya pendekatan biopsikososial dalam perencanaan terapi jangka panjang.